Digital dimension of entrepreneurship as a significant dimension of social security - Kovačević, Milan; Tomašević, Vladimir (Sociološki pregled, 2024)
Digital entrepreneurship represents an important component of economic development. This paper tries to emphasize the importance of the factors that belong to the digital dimension of the entrepreneurial ecosystem according to the EIDES methodology, in the early phase of the company’s life cycle, from the area of human capital. The goal is to point out the role of these factors in improving economic stability and the ability of individuals to effectively respond to the challenges and opportunities of the modern digital environment. Understanding the importance of this dimension becomes crucial when defining policies and strategies aimed at improving the quality of life of individuals and the social community as a whole, ensuring fair access to economic and professional opportunities of importance for social security in the 21st century.